Administrative justice as the element of globalization of human rights protection - Смокович, Михайло Іванович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
This article is devoted to the research of positive side of globalization of administrative justice and protection of human rights in Ukraine. Some aspects of globalization in administrative justice during settlement of conflicts arising from the public relations are determined there.